Prevalence of Amp C Beta-lactamase Producers Among Uropathogens at Shree Birendra Hospital. - Dhungel, Laxmi; Manandhar, Sarita; Bhatta, Sabita; Chaudhary, Raina (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Amp C β lactamases confer resistance to a wide variety of β-lactam antibiotics and are poorly inhibited by β-lactamase inhibitors such as clavulanic acid. Plasmid carrying Amp C enzyme also carry genes responsible of resistance to multiple other antibiotics, hence therapeutic options to infection caused by this type of organism is limited. Limited studies on prevalence of these organisms have been done in Nepal. The study is done to know the prevalence of Amp C β lactamase producers among the uropathogens. Methods: Amp C β lactamase producers were detected by double disc synergy test using the disc of cefoxitin (30μg) and cefoxitn (30μg) plus phenylboronic acid (20μl). An increase in zone diameter of ≥5mm to cefoxitin disc with phenylboronic acid versus cefoxitin alone was considered confirmed ABL producers. Result: The ABL production was found in 8.94% of the total isolates. It was observed in 9.87% of E. coli isolates and in 20% of Ps. aeruginosa. ABL producers were found to be resistant to many drugs when compared to Non-ABL producers. Conclusion: Amp C β lactamase producers were found among uropathogens. They were resistant to many antibiotics compared to Non- Amp C β lactamase producers. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.12991